Media Law. - Bloy, Duncan (SAGE course companions., 2006)
Media Law is part of an exciting new series from SAGE. It is designed to help students to make the most of their course in the subject. Developed as accessible reference tools, SAGE Course Companions offer an introduction to the subject and encourage students to extend their understanding of key concepts, issues and debates. This book provides a basic grounding in media law, alongside pointers to further reading and advice on study skills. It can be used as an overview of the subject and referred to throughout the degree for tips and revision guidance.